Legal Review of Conceptual Differences Between Folklore and Traditional Cultural Expressions in the Context of Intellectual Property Rights - Fikri Haikal, Muhammad (ASTONJADRO, 2024)
This research examines the differences between folklore and traditional cultural expressions in the context of intellectual property rights, especially in Article 20 paragraph (1) of the PTEBT Bill and Article 38 of the Copyright Law in Indonesia. This research applies normative juridical methods and descriptive analysis through secondary data in the form of journals, articles and other relevant data. Folklore is oral stories and old traditions without a clear creator, while Traditional Cultural Expressions include various aspects of cultural heritage such as fine arts, music, dance and clothing. This difference has meaning in protecting people's rights to their cultural heritage. Article 38 of the Copyright Law states state ownership of Copyright of Traditional Cultural Expressions, ordering the inventory, maintenance and preservation of cultural heritage as an integral part of national identity. Similar guidance is provided by the UNESCO Convention and the TRIPS Agreement. Implementation varies depending on national laws.